Comparison of citrate dialysate in pre- and post-dilution online hemodiafiltration: effect on clot formation and adequacy of dialysis in hemodialysis patients - Pasu Nakornchai; Arisara Jitraree; Monpinya Charttong Homjan; Thanachit Laykhram; Thananda Trakarnvanich (Renal Failure)
Background Citrate dialysate (CD) has been successfully used in conventional hemodialysis and continuous renal replacement therapy; however, no study has compared pre- and post-dilution online hemodiafiltration (oL-HDF). Therefore, we aimed to investigate the efficacy of citrate anticoagulation for oL-HDF and the metabolic changes and quality of life of patients on hemodialysis treated using both modesMethod Eight dialysis patients were treated with CD containing 0.8 mmol of citric acid for 4 weeks in each phase. Visual clotting scores were investigated as the primary endpoints. Adequacy of dialysis, laboratory parameters, and quality of life were measured as secondary objectives.Results The mean clotting scores in the pre-dilution mode were significantly lower than those in the post-dilution mode and in all phases except the heparin-free phase (p < 0.001 in the baseline phase, p = 0.001 in phase 1, and p = 0.023 in phase 2). The values of Kt/V in both modalities were comparable except during the baseline phase, in which the values of pre-dilution were significantly greater than post-dilution (2.36 ± 0.52/week vs. 1.87 ± 0.33/week;95% CI −0.81 to −0.19, p = 0.002). The patient’s quality of life regarding their physical activity level was significantly higher in the post-dilution mode than in the pre-dilution mode at baseline and in phase 1 (p = 0.014 and 0.004 at baseline and in phase 1, respectively). Metabolic changes did not differ between the two modes.Conclusion Citrate dialysate decreased or prevented anticoagulation in both pre- and post-dilution modes of oL-HDF without significant side effects and had comparable adequacy of dialysis.